2015
DOI: 10.1039/c5sm01051a
|View full text |Cite
|
Sign up to set email alerts
|

Curing kinetics and morphology of a nanovesicular epoxy/stearyl-block-poly(ethylene oxide) surfactant system

Abstract: Brittle epoxy based thermosets can be made tougher by introducing structural inhomogeneities at the micro- or nanoscale. In that respect, nano vesicles and worm-like micelles from self-assembling blockcopolymers have been shown to be very effective. This paper describes the curing kinetics and morphology of an epoxy composed of diglycidyl ether of bisphenol A (DGEBA) and 4,4'-methylenedianiline (MDA), modified by 20% of the surfactant stearyl-block-poly(ethylene oxide). Time resolved, synchrotron small-angle X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…27,28 Few studies have been reported on nanostructured epoxy networks modified with BCP vesicles. 4,[18][19][20][21][29][30][31][32][33] In most cases, vesicular aggregates were formed in the thermoset precursors before curing reaction, and then these were frozen by subsequent formation of the epoxy network. It was demonstrated that, under such conditions, vesicles can only be obtained within a very narrow concentration window.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Few studies have been reported on nanostructured epoxy networks modified with BCP vesicles. 4,[18][19][20][21][29][30][31][32][33] In most cases, vesicular aggregates were formed in the thermoset precursors before curing reaction, and then these were frozen by subsequent formation of the epoxy network. It was demonstrated that, under such conditions, vesicles can only be obtained within a very narrow concentration window.…”
Section: Introductionmentioning
confidence: 99%